Model predictive control for constrained systems with uncertain state-delays - Xiao-Bing Hu; Wen-Hua Chen (2004)
This paper presents a Model Predictive Control (MPC) algorithm for a class of constrained linear systems with uncertain state-delays. Based on a novel artificial Lyapunov function, a new stabilizing condition dependent of the upper bound of uncertain state-delays is presented in an LMI (Linear Matrix Inequality) form. The proposed MPC algorithm is developed by following the fashion of stability-enforced scheme. The new algorithm is then extended to linear time-varying (LTV) systems with multiple uncertain state-delays. Numerical examples illustrate the effectiveness of the new algorithm.